The use of voluntary disclosure in determining the quality of financial statements: Evidence from the Nigeria listed companies - Oluwagbemiga, Oyerogba Ezekiel (Serbian Journal of Management, 2014)
The purpose of this study was to establish the use of voluntary disclosure in determining the quality of financial statements among the listed companies in Nigeria. Specifically the study investigated on the effects of voluntary disclosure on investor decision and performance of listed companies in Nigeria. This study adopted an exploratory design which is described as a method of collecting information by interviewing or administering a questionnaire to a sample of individuals. The instrument of data collection for this research was a questionnaire as the study used primary data. The study targeted all the 258 listed companies in Nigeria. The study population used in this research comprised of preparers (accountants), external auditors and users of accounting information (financial analysts, stockbrokers, bankers, regulators and educators). The sample of this study was 140 whereby twenty questionnaires were distributed in every category of the respondents. Descriptive statistics such as mode, median, mean, standard deviation, etc were used to perform data analysis. These measures were calculated using Statistical Package for the Social Sciences (SPPS 20) software. SPSS tool (Statistical Package for the Social Sciences) was used to organize and analyze data. The study findings indicated that there was increased performance and investor decision making was easy to make due to voluntary disclosure. The results indicate that voluntary disclosure was satisfactory in explaining investor decision making and performance of listed companies. It was possible to conclude from the study findings that voluntary disclosure was statistically significant in explaining investor’s decision and performance of listed companies in Nigeria. It was also possible to conclude that there was high level of voluntary disclosure in Nigeria listed firms which led to high performance of the firms and made it easy for investors to make decision whether to invest in the companies or not.